Effect of Plantago lanceolata L. cultivar on nitrous oxide emissions from simulated cattle urine patches - Nicole Hammond; Jiafa Luo; Priscila Simon; Keren Ding; Racheal Bryant; Rainer Hofmann; Elena Minnée; Cecile de Klein (Agriculture, Ecosystems & Environment, 2026)

Influence of phosphorus fertiliser use on two New Zealand pasture insect pest communities - Katrin G. Hewitt; Rainer W. Hofmann; Olivier J. Ball; Chanatda Somchit; Colin M. Ferguson; Ray Moss; Racheal H. Bryant; Alison J. Popay (Agriculture, Ecosystems & Environment, 2025)

Results of the SSM-SICOPS melt tests of the EU-SAFEST project - Gert Langrock; Torsten Keim; Manfred Fischer; Matthias Braun; Sebastian Kohn; Roland Hofmann; Rainer Bezold; Martin Neumeister; Sevostian Bechta; Patrick Isaksson (Annals of Nuclear Energy, 2025)

Root aphid (Aploneura lentisci) population size on perennial ryegrass is determined by drought and endophyte strain - Katrin G. Hewitt; Rainer W. Hofmann; Oliver J. Ball; Neil Cox; Racheal H. Bryant; Sarah C. Finch; Alison J. Popay (Journal of Pest Science, 2024)
Climate change is anticipated to lead to an increase in the occurrence and intensity of drought and fluctuations in insect cycles that will challenge modern pasture systems. Feeding by root aphids such as Aploneura lentisci Pass. can be a significant challenge to pastures. These below-ground living aphids are commonly found in New Zealand and Australia, feeding year-round on the roots of graminaceous plants such as perennial ryegrass ( Lolium perenne L.). Some strains of the fungal endophyte Epichloë festucae var. lolii in perennial ryegrass can provide protection against root aphids and greater resilience under drought, contributing to higher persistency and growth than endophyte-free plants. However, the interaction between insect pressure and drought is not understood. This study examined the effect of drought on root aphid populations and plant performance in perennial ryegrass plants relative to endophyte status (±) and endophyte strain (AR37, NZ CT ) in a glasshouse experiment. Plants were cloned across the drought and well-watered treatments, and half of the plants were inoculated with root aphids, whilst half of the plants were treated with insecticide. Endophyte infection with strain NZ CT and AR37 reduced root aphid numbers. Aphid populations were significantly higher in drought-stressed than in well-watered plants in both endophyte-infected and endophyte-free treatments. Under drought conditions, root aphid populations were increased 4-fold in NZ CT and 8-fold in AR37 and endophyte-free plants in comparison with their well-watered counterparts. Root aphids reduced shoot dry weight by 16% in drought-exposed and 26% in well-watered plants in comparison with their insecticide-treated counterparts whilst reducing root biomass by 49%. Our results suggest that root aphids are likely able to exploit the higher availability of amino acids in the plant sap of drought-exposed plants. This study provides evidence that climate change-mediated impacts of root aphids could reduce production in perennial ryegrass-dominant pastures. However, field trials would be necessary to determine whether this effect is seen in situ, where numerous additional factors will be operating at the same time.

Soluble PD-L1 in blood correlates positively with neutrophil and negatively with lymphocyte mRNA markers and implies adverse sepsis outcome - Marcus Derigs; Hendrik Heers; Susanne Lingelbach; Rainer Hofmann; Jörg Hänze (Immunologic Research, 2022)
Sepsis causes a myriad of immunological reactions that result in life-threatening alterations in the human body. Immunosuppression in sepsis is partly attributed to the programmed death receptor (PD-1) and its associated ligand (PD-L1) via the regulation of lymphocytes and neutrophils. Although the soluble forms of these proteins (i.e., sPD-1 and sPD-L1, respectively) are recognized as possible sepsis biomarkers, their functional implications are yet to be elucidated. Our research assessed the correlation between sPD-1 and sPD-L1 and blood mRNA markers and sepsis outcome. Blood samples of septic patients of urogenital origin versus control patients (both groups: n = 18) were analyzed. Blood serum sPD-1 and sPD-L1 levels were determined using the enzyme-linked immunosorbent assay (ELISA). The whole blood mRNA concentrations of PD-1, PD-L1, neutrophil markers (CEACAM8 and MPO), and T-lymphocyte markers (TCRβ, CD4 and CD8) were determined via reverse transcriptase quantitative PCR (RT-qPCR). sPD-L1 levels were significantly increased in septic patients when compared to the controls, whereas sPD-1 levels were unaltered. Patients with high sPD-L1 levels, as dichotomized to the median, had a significantly shorter survival rate than those with low sPD-L1 levels. The sensitivity/specificity characteristics of sPD-L1 proved significant for sepsis detection. Furthermore, sPD-L1 correlated with the mRNA concentrations of PD-L1, CEACAM, and MPO, as well as major inflammatory markers (C-reactive protein and procalcitonin). However, sPD-L1 negatively correlated with TCRβ, CD4, and CD8 mRNAs. sPD-L1 was found to be significantly increased in septic patients. Notably, sPD-L1 correlated with PD-L1 mRNA and neutrophil markers and was indicative of adverse outcomes.

A Theoretical Framework for the Evaluation of Massive Digital Participation Systems in Urban Planning - Mathias Hofmann; Sander Münster; Jörg Rainer Noennig (Journal of Geovisualization and Spatial Analysis, 2020)
Urban development that strives to meet democratic ideals and the needs of all stakeholders must incorporate public participation. Contemporary participation processes may employ digital tools that open new possibilities regarding the range of participants and the intensity of participation. In particular, they can uniquely allow for large and diverse groups of participants to be involved in collaborative design processes. Evaluating such processes is important because it allows for the justification of the necessary costs and efforts, as well as continuous improvement. Using the phases specified in the minimal viable process of the U_CODE project as an example, this paper aims at describing criteria for the evaluation of participation processes and propose several possible methods for their assessment. While the majority of these criteria resemble criteria traditionally used to assess public participation in general, this paper proposes an additional criterion, as well as ways of applying all of the criteria to digital participation methods. In addition, the criteria and methods described in this paper not only may be used for evaluative purposes during or after a digital participation process but may also be useful guidelines during the planning stages of participation processes. Hence, it may help to consider these criteria to assess the value of the process during its inception stage to avoid mistakes and to enhance the democratic value of the participation process.

Systemic LPS induces toll-like receptor 3 (TLR3) expression and apoptosis in testicular mouse tissue - Lene N. Nejsum; Adrian Piec; Monika Fijak; Christina V. Ernstsen; Dania Fischer; Thorsten J. Maier; Ralf Kinscherf; Rainer Hofmann; Anja Urbschat (Cell and Tissue Research, 2019)

Exotic plant species are locally adapted but not to high ultraviolet‐B radiation: a reciprocal multispecies experiment - Maria Hock; Rainer W. Hofmann; Caroline Müller; Alexandra Erfmeier (Ecology, 2019)
Ultraviolet ( UV ) radiation intensities differ among global regions, with significantly higher levels in the southern hemisphere. UV ‐B may act as an environmental filter during plant invasions, which might particularly apply to plant species from Europe introduced to New Zealand. Just like for any other abiotic or biotic filter, successful invaders can cope with novel environmental conditions via plastic responses and/or through rapid adaptation by natural selection in the exotic range. We conducted a multispecies experiment with herbaceous plants in two common gardens located in the species’ native and exotic ranges, in Germany and New Zealand, respectively. We used plants of German and New Zealand origin of eight species to test for adaptation to higher UV ‐B radiation in their new range. In each common garden, all plants were exposed to three radiation treatments: (1) ambient sunlight, (2) exclusion of UV ‐B while transmitting ambient UV ‐A, and (3) combined exclusion of UV ‐B and UV ‐A. Linear mixed‐effect models revealed significant effects of UV ‐B on growth and leaf traits and an indication for UV ‐B‐induced biomass reduction in both common gardens pointing to an impact of natural, ambient UV radiation intensities experienced by plants in the northern and in the southern hemisphere. In both common gardens, the respective local plants (i.e., German origins in Germany, New Zealand origins in New Zealand) displayed enhanced productivity and aboveground biomass allocation, thus providing evidence for recent evolutionary processes in the exotic range. Genetic differentiation between different origins in consequence of divergent local selection pressures was found for specific leaf area. This differentiation particularly hints at different selective forces in both ranges while only little evidence was found for an immediate selective effect of high UV ‐B intensities in the exotic range. However, reaction norm slopes across ranges revealed higher plasticity of exotic individuals in functional leaf traits that might allow for a more sensitive regulation of photoprotection measures in response to UV ‐B. During the colonization, New Zealand populations might have been selected for the observed higher phenotypic plasticity and a consequently increased ability to successfully spread in the exotic range.

Seroprevalence study in forestry workers from eastern Germany using novel genotype 3- and rat hepatitis E virus-specific immunoglobulin G ELISAs - Paul Dremsek; Jürgen J. Wenzel; Reimar Johne; Mario Ziller; Jörg Hofmann; Martin H. Groschup; Sandra Werdermann; Ulrich Mohn; Silvia Dorn; Manfred Motz; Marc Mertens; Wolfgang Jilg; et al. (Medical Microbiology and Immunology, 2012)

Seroprevalence study in forestry workers of a non-endemic region in eastern Germany reveals infections by Tula and Dobrava–Belgrade hantaviruses - Marc Mertens; Jörg Hofmann; Rasa Petraityte-Burneikiene; Mario Ziller; Kestutis Sasnauskas; Robert Friedrich; Olaf Niederstrasser; Detlev H. Krüger; Martin H. Groschup; Eckhardt Petri; Sandra Werdermann; Rainer G. Ulrich (Medical Microbiology and Immunology, 2011)

Obesity is associated with improved survival in patients with organ-confined clear-cell kidney cancer - Sandra Waalkes; Axel S. Merseburger; Mario W. Kramer; Thomas R. W. Herrmann; Gerd Wegener; Julia Rustemeier; Rainer Hofmann; Mark Schrader; Markus A. Kuczyk; Andres J. Schrader (Cancer Causes & Control, 2010)

Sensitivity of white clover to UV‐B radiation depends on water availability, plant productivity and duration of stress - RAINER W. HOFMANN; BRUCE D. CAMPBELL; DAVID F. FOUNTAIN (Global Change Biology, 2003)
Nine populations of white clover ( Trifolium repens L.) were grown for 12 weeks with supplemental application of 13.3 kJ m −2 d −1 ultraviolet‐B (UV‐B) radiation under controlled environmental conditions. Drought was applied during the last four weeks of the experiment. Under well‐watered conditions, UV‐B decreased white clover growth on average by 20%. Cultivars bred for agricultural performance were sensitive to UV‐B, while slow‐growing ecotypes were UV‐B‐tolerant. After four weeks of water stress, there were no significant population differences in UV‐B responsiveness. UV‐B sensitivity decreased with increasing exposure to drought and with longer duration of UV‐B irradiation, suggesting that the direction and extent of the UV‐B 3× drought interaction depends on the duration of stress. The population comparisons indicate that low constitutive growth rate and adaptation to other forms of stress may be related to UV‐B tolerance under well‐watered conditions, but not during extended periods of drought.

Molecular structures and associations of humic substances in the terrestrial environment - André J. Simpson; William L. Kingery; Michael H. Hayes; Manfred Spraul; Eberhard Humpfer; Peter Dvortsak; Rainer Kerssebaum; Markus Godejohann; Martin Hofmann (The Science of Nature, 2002)